Investigation and implementation of image processing algorithms for medical application - Mya Thandar Maung. (2013)
Functional Magnetic Resonance Imaging (fMRI) has experienced a rapid growth in the past several years and has found further applications in a wide variety of fields, such as neuroscience, psychology, and political science, in addition to medical applications. Currently, there exist a number of different imaging modalities that allows the users to study the physiological changes that accompany brain activation. Each of these techniques provides a unique perspective on brain function and meeting the individual purposes. Among them, there has been a growing number of neuro-imaging studies performed using fMRI. The fMRI is now solidly established as a noninvasive diagnostic technique in acquisition of physiological and biochemical information and in particular for studying brain activity, as well as tumors and cancerous vicinity. The fMRI takes advantage of the relationship of certain stimuli leads to initiate changes in neuronal activity, which give momentary changes in blood oxygenation/oxygen level (BOLD) to the active region of the brain. In practice, it identifies the brain activity by picking up minute changes in blood flow in response to stimuli that the subject or patient experiencing associated with alternative non-stimulated instance or pause while the scanning is in progress. Changes in the measured signal between individual images are to make inferences regarding task-related activations in the brain.